PEMBUATAN PANDUAN DIGITAL UNTUK PENDAMPINGAN IMPLEMENTASI APLIKASI AKUNTANSI SISTEM KEUANGAN BAGI KONGREGASI SUSTER-SUSTER AMAL KASIH DARAH MULIA - Effendi, Sukma Meganova; Widodo, Bernardinus Sri; Sinaga, Klemensia Erna Christina; Anurogo, Baskoro Latu; Yudianti, Ninik; Ria, Angelita Martina Loy; Agustinus, Kevin (Universitas Sanata Dharma, 2024)
Users of the Financial System in this community service activity are Congregation of Sisters of Charity of Noble Blood (ADM). They have a variety of ages and educational backgrounds, so most users do not really understand how to operate and categorize transactions according to transaction codes. This activity is held to help users using the Financial System by making digital guides. The method used is this activity is the discussion method by evaluating the Financial System which has been used in exploring problems, making digital guides (documents and videos), adding digital guides to the Financial System, and socializing the Financial System which has added digital guides. As a result, there are two digital guidance documents. The first is a Chart of Account (COA) book which contains transaction codes and the second is a Manual Book which contains how to operate the Financial System. The other results, there are two video tutorials that explain the entire operation method and especially, the transaction and report sections. The digital guide that has been added to the Financial System is quite helpful for users in operating it, where 13 respondents gave the most ratings in very good, good, and good enough conditions.